Using Three-Component Data for Seismic Interferometry Studies at the Kylylahti Mine, Eastern Finland - Väkevä, Sakari (Helsingin yliopisto, 2019)
The reflection seismic surveying method is useful when conducting mineral exploration in the crystalline bedrock because of its good depth extent and resolution. However, the traditional experiments with active sources are expensive and difficult to carry out, especially in remote areas or in conservation areas where mineral exploration is limited due to environmental reasons. Recently, a number of theoretical advances have proven that passive soundings utilizing ambient seismic noise can provide new opportunities for seismic imaging and contribute to data generation for reflection seismic surveys, without the need for explosive or vibratory sources. One of the most promising new methods is seismic interferometry (SI), where the impulse response between two receivers is reconstructed by correlating their signals with each other. COGITO-MIN is a joint project between the University of Helsinki, the Geological Survey of Finland, Polish Academy of Sciences, and industrial partners with the aim of investigating and developing new cost-effective seismic exploration methods in the crystalline bedrock. Within the framework of the project, a passive seismic experiment was carried out in which 45 three-component geophones were deployed for a month in the vicinity of the polymetallic Kylylahti Mine in Polvijärvi, northern Karelia, where the mining operator is the Swedish metal company Boliden. The original purpose of these geophones was to collect data suitable for detecting underground cavities related to underground nuclear explosions. The institute that collected the data was CTBTO (Comprehensive Test Ban Treaty Organization) whose task is to monitor the treaty in the pre-ratification stage. The purpose of this Master's thesis was to develop an SI workflow for the three-component data and to investigate the method's performance in an area where local geology is known after nearly 40 years of exploration and consequent mining operations. The specific scientific objectives of the thesis are (1) to demonstrate the ...